2021
DOI: 10.1186/s12936-021-03722-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the durability of long‐lasting insecticidal nets in Guatemala

Abstract: Background Insecticide-treated bed nets (ITNs) are widely used for the prevention and control of malaria. In Guatemala, since 2006, ITNs have been distributed free of charge in the highest risk malaria-endemic areas and constitute one of the primary vector control measures in the country. Despite relying on ITNs for almost 15 years, there is a lack of data to inform the timely replacement of ITNs whose effectiveness becomes diminished by routine use. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
1
10
1
Order By: Relevance
“…This study also showed that while inducing high mortality compared to P2, IG2 aged induced signi cantly low mortality compared to new IG2. This could be due to a decrease in the insecticide content over time of ITNs in operational use, as demonstrated in several studies (43,44). In contrast, Martin et al(45) have demonstrated that after 20 washes (supposed to mimic a 36 months eld net) IG2 washed did not induce a signi cantly different mortality from IG2 unwashed, con rming the wash resistance of this net.…”
Section: Discussionmentioning
confidence: 91%
“…This study also showed that while inducing high mortality compared to P2, IG2 aged induced signi cantly low mortality compared to new IG2. This could be due to a decrease in the insecticide content over time of ITNs in operational use, as demonstrated in several studies (43,44). In contrast, Martin et al(45) have demonstrated that after 20 washes (supposed to mimic a 36 months eld net) IG2 washed did not induce a signi cantly different mortality from IG2 unwashed, con rming the wash resistance of this net.…”
Section: Discussionmentioning
confidence: 91%
“…gambiae, Anopheles stephensi, Anopheles albimanus, Anopheles culicifacies, Anopheles arabiensis, Aedes aegypti and Culex quinquefasciatus from across various continents (Oceania, Asia, Africa and the Americas), as well as in mosquito colonies reared in European laboratories. A non-exhaustive list of these studies with confirmed pre-2013 PermaNet ® 2.0 nets includes the following studies (24 h mortality rates obtained with WHO cone bioassays are provided in parentheses): Katusele et al (100%) [ 20 ]; Kilian et al (100%) [ 21 ]; Castellanos et al (100%) [ 22 ]; Graham et al (100%) [ 23 ]; Kweka et al (100%) [ 24 ]; Okia et al (100%) [ 25 ]; Sreehari et al (100%) [ 26 ]; Kayedi et al (100%) [ 27 ]; Jarramillo et al (100%) [ 28 ]; Dery et al (100%) [ 29 ], and Sood et al (100%) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most promising alternative methods is x-ray fluorescence (XRF) spectroscopy. Researchers in Ghana, Ethiopia and Guatemala have demonstrated the utility of XRF for fast quantification of deltamethrin in the field, specifically, for durability assessment of PermaNet® LLINs after (3 -38) months of use [8, 24, 25]. While XRF has been shown to be able to quantify deltamathrin, little is known if this concept has been applied to other insecticides even though this is theoretically possible using the same methodology.…”
Section: Introductionmentioning
confidence: 99%